Management Qur'anic Healing as a Complement to Medical Therapy - Puput Mulyono; Singgih Purnomo (Jurnal Visi Manajemen, 2024)
Background: Present day clinical remedies are only symptomatic, requiring complementary therapies to cure the patient. Purpose: The reason of this have a look at is to find out how analyzing and being attentive to the Qur'an is used as remedy or Qur'anic remarkable recovery. Methods: This studies makes use of a qualitative technique with a form of library studies (look at Library). Results: The first studies degree explains the meaning of reading and listening in addition to the manners in studying and taking note of Qur'an. The second one degree is set the idea of Qur'anic wonderful restoration, 0.33 level is explaining the shortcomings and blessings of Qur'anic first-rate recovery to complement clinical therapy. The remaining stage closes with conclusions and hints. Conclusion: Taking note of the Qur'an as a therapy by analyzing the verses of the Qur'an with fami bi shaqin or Qur'anic tremendous recuperation technique, the verse signals that we see will input the mind then the meaning of the verse occurs. The interpretation of the verse that is seen contains the content of spiritual values in the Al-Qur'an surah which teaches a positive attitude that recognizes Allah, gratitude, compassion, optimism, humility, and mental toughness in facing trials from Allah SWT will be processed in the brain in such a way as to produce positive reactions that make a person steadfast and optimistic so that health conditions improve.